TREND KAJIAN PEMBELAJARAN DARING: SUATU TELAAH PUSTAKA - Sanita Martiara Tauhid; Nurmalasari Nurmalasari; Fantrido Foldra; Roni Jayawinangun (Jurnal Penelitian Sosial Ilmu Komunikasi, 2020)
This study aims to determine research trends related to online learning and the effectiveness of online learning. The study used a qualitative approach with the online literature review method where in collecting data information with documentation techniques, namely looking for data on relevant matters from various online sources such as journals, research results, documents, books, magazines, news. The criteria for the articles and news chosen were a discussion of the online learning process. The results of this study from 40 articles collected showed that the trend of online learning research was dominated by a qualitative approach, followed by quantitative and combined methods using primary and secondary data. As for data collection using interviews, observation, participatory. The data analysis used was descriptive analysis, literature review and experimental. Learning is considered effective before the pandemic by 58.8%, decreasing at the time of the pandemic by 41.2%. Based on the level of early childhood education, primary schools, secondary schools and tertiary institutions are considered effective, but in practice there is still a need for improvement to be better. Keyword : effectiveness; literature review; online learning; trend of online learning.